ANALISIS KESADARAN MASYARAKAT MENGENAI PENTINGNYA MENJAGA KEBERSIHAN LINGKUNGAN DI SEKITAR JALAN JENDERAL SUDIRMAN PENGGUNG - Bila, Salsa; Wulandari, Nadila; Ulia, Almas Ressul (CV. Kalimasada Group, 2024)
The purpose of this study is to analyze public awareness of the importance of maintaining the cleanliness of the environment around Jalan Jenderal Sudirman which is one of the strategic and active areas of the city of Cirebon. The research method used is a descriptive qualitative approach which includes field observations, in-depth interviews with communities working or operating around Jalan Jenderal Sudirman, and documentation. Observations showed a lot of garbage on the side of the road, even though the trash can had been laid out. Meanwhile, from the results of interviews, it is known that most people are aware of the importance of maintaining the cleanliness of the environment, but there are still many who do not care and do not want to throw garbage in its place. Factors contributing to low public awareness include lack of education and socialization, lack of supervision and law enforcement, and low individual awareness and sense of responsibility. Some suggestions that can be given to increase public awareness include improving education and socialization, increasing supervision and enforcement of regulations, and developing programs that involve the community in maintaining environmental cleanliness.